Molecular Detection of Tick-Borne Bacterial Pathogens in Ticks and Rodents from the China–Vietnam Border - Hongbo Liu; Wenwei Xiao; Xinying Du; Jingzhuang Xue; Hui Wang; Qi Wang; Yule Wang; Huiqun Jia; Hongbin Song; Shaofu Qiu (Veterinary Sciences)
Ticks and tick-borne diseases constitute a crucial focus for the health of both humans and animals worldwide. Although numerous studies on tick-borne diseases have been conducted in China, reports on tick-borne pathogens in ticks and rodents from the China–Vietnam border are scarce. In this study, we investigated tick-borne bacterial pathogens, including Rickettsia, Anaplasmataceae, and Borrelia, in nine rodents (Rattus norvegicus) and 88 ticks collected from cattle and rodents in Jingxi, a city at the China–Vietnam border. Through molecular detection and sequence analysis, four known tick-borne pathogens were identified. Specifically, Rickettsia japonica was detected in 46.3% (37/80) of Haemaphysalis cornigera; Anaplasma phagocytophilum and Candidatus Neoehrlichia mikurensis were identified in one Ixodes granulatus and one rodent, respectively; and Borrelia valaisiana was detected in two I. granulatus. Additionally, a potentially novel species of Rickettsia, provisionally named Rickettsia sp. JX, was detected in 41.3% (33/80) of Ha. cornigera, one Rhipicephalus microplus, three I. granulatus, and nine rodents, whereas a potentially novel species of Borrelia, tentatively named Borrelia sp. JX, was detected in one I. granulatus. To the best of our knowledge, this is the first report on tick-borne bacterial pathogens in ticks and rodents from the China–Vietnam border. These results expand the knowledge of the geographical distribution and vector diversity of tick-borne bacterial pathogens in China and are conducive to the evaluation of thee potential public health risk.